Abū Nūwās Sanctifying the Profane and Tarnishing the Sacred in His Poetry: An Anthropological Approach - Almutairi, Ahmad Hamad; Alajmi, Hamad Obaid (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to analyze the poetry of Abu Nawas on wine and debauchery as a deliberate process of sanctifying the profane and desecrating the sacred in Arab and Islamic culture. The study also seeks to provide a historical and cultural context to understand the role of this model of Abu Nawas' poetry in the Abbasid era. Additionally, the study aims to offer a new understanding of Abu Nawas' model and his poetry as a representation of what we call the social margin, which works to subvert the social norms of his time, referred to as the social text. Methods: This study adapts an epistemological approach utilizing several anthropological concepts to analyze the motivations that led Abū Nūwās’ poetry to manifest in such manner. Some of the key concepts used are Mary Douglas’ concept of marginality, Marcea Eliade’s concept of the sacred and the profane, Van Gennep’s rites of passage, and Victor Turner’s concept of communitas. Results: The study concludes that Abu Nawas' poetry of this kind seeks to sanctify the profane and desecrate the sacred, valued and believed in by the social center (the social text). The study also finds that this sanctification and desecration in Abu Nawas' poetry are a means to dismantle the norms of the social text and its sanctities, aiming to destabilize cultural boundaries and dissolve social differences between the social text and the margin. Conclusion: The study concludes that this type of poetry by Abu Nawas originated from a marginalized social condition that the poet experienced. His poetry emerged as a discourse stemming from this disgruntled marginal state, challenging the norms of the social text. Therefore, the study recommends leveraging concepts from anthropology and sociology to study and analyze Arabic poetry and the social conditions experienced by the poet.